Mycobacterium abscessus prosthetic valve endocarditis in a patient with Marfan syndrome. Issue 5 (10th September 2015) - Tennant, Sarah J.; Forster, Derek W.; Burgess, Donna R.; Huaman, Moises A.
Abstract : Introduction: Mycobacterium abscessus is a non-tuberculous mycobacterium ubiquitous in the environment, which rarely causes endovascular infections. We report the first published case, to the best of our knowledge, of M. abscessus endocarditis in a patient with Marfan syndrome. Case presentation: A female in her 40s with a history of Marfan syndrome status-post mechanical aortic valve replacement and a chronic indwelling venous access port presented with a 2-day history of confusion and 3-month history of intermittent fevers. Her blood cultures grew M. abscessus . An echocardiogram revealed a 1 cm vegetation attached to the prosthetic aortic valve and a perivalvular abscess. The patient was started on imipenem/cilastatin, amikacin and linezolid. Her course was complicated by septic emboli to the brain and subarachnoid haemorrhage. She was deemed a poor surgical candidate. The patient ultimately developed cardiac arrest and died. Conclusion: M. abscessus endocarditis is rare and is associated with high mortality. Late recognition of M. abscessus as a causative pathogen of endovascular infection, extensive antimicrobial resistance and limited surgical options at the time of diagnosis make the management of M. abscessus endocarditis very challenging.